The Elephant Trunk Technique: A New Complication - Neri, Eugenio (2001)
We describe a complication that occurred during the 2nd stage of an “elephant trunk” aortic replacement. The patient was a 58-year-old woman who had undergone graft replacement of the ascending aorta and aortic arch with the elephant trunk technique for an acute, Stanford type-A aortic dissection.